2023
DOI: 10.3390/nu15071618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Maca Supplementation on Inflammatory Markers and Physical Fitness in Male Elite Athletes

Abstract: Given the current lack of studies, the primary purpose of this study was to investigate the effects of black maca supplementation intake on changes in physical strength and inflammatory markers among elite athletes. Forty-four elite athletes were recruited for the present study. They included shooting athletes, racket sports athletes, and fin swimming athletes. The intake capsules contained 2500 mg of 100% concentrated black maca extract. Participants were instructed to take one capsule twice a day for eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Summary of published clinical trials using black maca, modified from [182]. [173] in 40 elite athletes: shooting athletes (SA), racket sports athletes (RSA), fin swimming athletes (FSA) Species: Lepidium meyenii Product: Not stated Location/Cultivation: Not stated Form: 100% concentrated black maca extract Dose and Route: 2300 mg twice daily in the AM and PM Evaluation of parameters using a digital grip dynamometer and a battery of physical exercises revealed significant increases after black maca supplementation in muscle endurance (p < 0.01 for SA group, p < 0.05 for RSA group), agility (p < 0.05 for SA and RSA groups), muscle strength (p < 0.01 for FSA group), flexibility (p < 0.01 for FSH group), and power (p < 0.05 for RSA group; p < 0.001 for FSA group. After taking black maca for eight weeks, significant differences in lactic acid (mg/dL) (p < 0.05) and total cholesterol (TC, mg/dL) were noted in the SA group (p < 0.01); TC (p < 0.01) and CRP (p < 0.01) in the RSA group; and lactic acid (p < 0.05), TC (p < 0.001), and CRP (p < 0.001) in the FSA group.…”
Section: Clinical Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Summary of published clinical trials using black maca, modified from [182]. [173] in 40 elite athletes: shooting athletes (SA), racket sports athletes (RSA), fin swimming athletes (FSA) Species: Lepidium meyenii Product: Not stated Location/Cultivation: Not stated Form: 100% concentrated black maca extract Dose and Route: 2300 mg twice daily in the AM and PM Evaluation of parameters using a digital grip dynamometer and a battery of physical exercises revealed significant increases after black maca supplementation in muscle endurance (p < 0.01 for SA group, p < 0.05 for RSA group), agility (p < 0.05 for SA and RSA groups), muscle strength (p < 0.01 for FSA group), flexibility (p < 0.01 for FSH group), and power (p < 0.05 for RSA group; p < 0.001 for FSA group. After taking black maca for eight weeks, significant differences in lactic acid (mg/dL) (p < 0.05) and total cholesterol (TC, mg/dL) were noted in the SA group (p < 0.01); TC (p < 0.01) and CRP (p < 0.01) in the RSA group; and lactic acid (p < 0.05), TC (p < 0.001), and CRP (p < 0.001) in the FSA group.…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Using spray-dried extracts, Zevallos-Concha et al found that black maca had greater polyphenol content and antioxidant potential than red maca [ 172 ]. Its high polyphenol level and antioxidant potential, while also shared by red maca, may be responsible, in part, for some of its functions listed below, including its ability to increase physical endurance [ 172 , 173 ].…”
Section: Black Macamentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were instructed to take one capsule twice a day with water for 4 weeks, without any designated time of day. BM intake was determined using methods described in previous studies (11).…”
Section: Measurement Of Physical Fitness and Isokinetics Muscular Per...mentioning
confidence: 99%